Coproduction of EPA and Fucoxanthin with P. tricornutum – A Promising Approach for Up‐ and Downstream Processing. Issue 11 (9th September 2020) - Derwenskus, Felix; Schäfer, Benjamin; Müller, Jan; Frick, Konstantin; Gille, Andrea; Briviba, Karlis; Schmid‐Staiger, Ulrike; Hirth, Thomas
Abstract: Eicosapentaenoic acid (EPA) and fucoxanthin, a carotenoid, provide a broad variety of health benefits in human nutrition. In this study, an up‐ and downstream process for the coproduction of EPA and fucoxanthin using the diatom Phaeodactylum tricornutum in flat‐panel airlift photobioreactors is proposed. The approach represents a promising alternative to conventional sources for both compounds, viz. marine fish and macroalgae. The productivity as well as the biomass‐specific product content were optimized during cultivation. Subsequently, both compounds were extracted, separated and purified using pressurized liquids. Abstract : A novel approach for up‐ and downstream processing of EPA and fucoxanthin using the diatom P. tricornutum derived from flat‐panel airlift photobioreactors is proposed in this study. This process represents a promising alternative to conventional production processes based on marine fish and macroalgae.